2021
DOI: 10.1152/ajpheart.00373.2020
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-107 antagonizes profibrotic phenotypes of pericytes by targeting a pathway involving HIF-1α/Notch1/PDGFRβ/YAP1/Twist1 axis in vitro

Abstract: Background: Microvascular pericytes have been demonstrated as an origin for myofibroblasts that produce excessive extracellular matrix (ECM) proteins such as α-smooth muscle actin (α-SMA) and type I collagen (ColI), and contribute to pulmonary fibrosis (PF). However, the signaling mechanism responsible for ECM production within pericytes is poorly understood. In this study, we examined exosomal miR-107 in the fibrotic phenotypes of pericytes and pathogenesis of PF. Methods: MiR-107 level was compared between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Moreover, the function of exosomes depends strongly on stimulation conditions and microenvironments-for example, Działo et al found that Wnt5a-enriched exosomes activated the ERK1/2 and JNK pathways, induced the production of IL-6, and promoted fibrosis (23). Wang et al showed that miR-107 in vascular endothelial cell-derived exosomes could alleviate fibrosis through the HIF-1α/Notch1/PDGFRβ/YAP1/Twist1 pathway (24). Thus, we investigated the impact of exosomes on atrial fibrosis in a canine model of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the function of exosomes depends strongly on stimulation conditions and microenvironments-for example, Działo et al found that Wnt5a-enriched exosomes activated the ERK1/2 and JNK pathways, induced the production of IL-6, and promoted fibrosis (23). Wang et al showed that miR-107 in vascular endothelial cell-derived exosomes could alleviate fibrosis through the HIF-1α/Notch1/PDGFRβ/YAP1/Twist1 pathway (24). Thus, we investigated the impact of exosomes on atrial fibrosis in a canine model of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes from pulmonary microvascular endothelial cells contained miR-107, which inhibited hypoxia inducible factor-1α ( HIF-1α ) in pericytes, resulting in suppression of a Notch1/PDGFRβ/yes associated protein 1 (YAP1)/Twist1 axis and downstream inhibition of αSMA and collagen 1α1 expression [ 78 ]. During pulmonary fibrosis, endothelial cell EV miR-107 levels were downregulated, resulting in enhanced HIF-1α expression and stimulation of pericyte transdifferentiation and fibrogenesis [ 78 ].…”
Section: Pulmonary Fibrosismentioning
confidence: 99%
“…Thus, the overexpression of miR-627 reduces TGF-1-induced changes in NHLFs and significantly reverses the excessive EMC deposition caused by overexpression of miR155HG. Microvascular pericytes are the source of excess ECM protein produced by myofibroblasts, contributing to PF ( 90 ). miR-107 expression has been shown to be reduced in clinical or experimental mouse PF tissue samples and exosomes by PF-derived microvascular endothelial cells ( 90 ).…”
Section: Role Of Micrornas In the Pathogenesis Of Pulmonary Fibrosismentioning
confidence: 99%
“…Microvascular pericytes are the source of excess ECM protein produced by myofibroblasts, contributing to PF ( 90 ). miR-107 expression has been shown to be reduced in clinical or experimental mouse PF tissue samples and exosomes by PF-derived microvascular endothelial cells ( 90 ). The anti-fibrotic effect of miR-107 is mediated by the inhibition of the hypoxia inducible factor 1 α (HIF-1α)/Notch1/platelet-derived growth factor receptor β (PDGFRβ)/Yes 1-associated transcriptional regulator/Twist1 signaling pathway.…”
Section: Role Of Micrornas In the Pathogenesis Of Pulmonary Fibrosismentioning
confidence: 99%